Skin innervation at different depths correlates with small fibre function but not with pain in neuropathic pain patients - Schley, Marcus; Bayram, Ayse; Rukwied, Roman; Dusch, Martin; Benrath, Justus; Schmelz, Martin (European journal of pain, 2012)
Background Neuropathy can lead not only to impaired function but also to sensory sensitization. We aimed to link reduced skin nerve fibre density in different levels to layer-specific functional impairment in neuropathic pain patients and tried to identify pain-specific functional and structural markers. Methods In 12 healthy controls and 36 patients with neuropathic pain, we assessed clinical characteristics, thermal thresholds (quantitative sensory testing) and electrically induced pain and axon reflex erythema. At the most painful sites and at intra-individual control sites, skin biopsies were taken and innervation densities in the different skin layers were assessed. Moreover, neuronal calcitonin gene-related peptide staining was quantified. Results Perception of warm, cold and heat pain and nerve fibre density were reduced in the painful areas compared with the control sites and with healthy controls. Warm and cold detection thresholds correlated best with epidermal innervation density, whereas heat and cold pain thresholds and axon reflex flare correlated best with dermal innervation density. Clinical pain ratings correlated only with epidermal nerve fibre density (r = 0.38, p < 0.05) and better preserved cold detection thresholds (r = 0.39, p < 0.05), but not with other assessed functional and structural parameters. Conclusions Thermal thresholds, axon reflex measurements and assessment of skin innervation density are valuable tools to characterize and quantify peripheral neuropathy and link neuronal function to different layers of the skin. The severity of small fibre neuropathy, however, did not correspond to clinical pain intensity and a specific parameter or pattern that would predict pain intensity in peripheral neuropathy could not be identified.